Number of Unfavorable Intermediate‐Risk Factors Predicts Pathologic Upstaging and Prostate Cancer‐Specific Mortality Following Radical Prostatectomy: Results From the SEARCH Database. Issue 2 (29th September 2016) - Zumsteg, Zachary S.; Chen, Zinan; Howard, Lauren E.; Amling, Christopher L.; Aronson, William J.; Cooperberg, Matthew R.; Kane, Christopher J.; Terris, Martha K.; Spratt, Daniel E.; Sandler, Howard M.; Freedland, Stephen J.
Abstract : BACKGROUND: To validate and further improve the stratification of intermediate risk prostate cancer into favorable and unfavorable subgroups for patients undergoing radical prostatectomy. MATERIALS AND METHODS: The SEARCH database was queried for IR patients undergoing radical prostatectomy without adjuvant radiotherapy. UIR disease was defined any patient with at least one unfavorable risk factor (URF), including primary Gleason pattern 4, 50% of more biopsy cores containing cancer, or multiple National Comprehensive Cancer Network IR factors. RESULTS: One thousand five hundred eighty‐six patients with IR prostate cancer comprised the study cohort. Median follow‐up was 62 months. Patients classified as UIR were significantly more likely to have pathologic high‐risk features, such as Gleason score 8 − 10, pT3–4 disease, or lymph node metastases, than FIR patients ( P  < 0.001). Furthermore, UIR patients had significantly higher rates of PSA‐relapse (PSA, hazard ratio [HR] = 1.89, P  < 0.001) and distant metastasis (DM, HR = 2.92, P  = 0.001), but no difference in prostate cancer‐specific mortality (PCSM) or all‐cause mortality in multivariable analysis. On secondary analysis, patients with ≥2 URF had significantly worse PSA‐RFS, DM, and PCSM than those with 0 or 1 URF. Moreover, 40% of patients with ≥2 URF had high‐risk pathologic features. CONCLUSIONS: Patients with UIR prostate cancer are at increased risk of PSA relapse, DM, and pathologic upstaging following prostatectomy. However, increased risk of PCSM was only detected in those with ≥2 URF. This suggests that further refinement of the UIR subgroup may improve risk stratification. Prostate Prostate 77:154–163, 2017 . © 2016 Wiley Periodicals, Inc.